An assessment of the persistence of putative pathogenic bacteria in chloraminated water distribution systems. (15th February 2021) - Bal Krishna, K.C.; Sathasivan, Arumugam; Ginige, Maneesha P.
Highlights: The diverse group of putative pathogenic bacteria are chloramine resilient. Mycolicibacterium fortuitum dominates at high chloramine residuals. 31 putative pathogenic bacterial species were abundant in chloraminated systems. Metagenomic surveillance enables an early warning of waterborne pathogen outbreaks. Future studies should focus on developing new indicator organisms. Abstract: This study investigated how a chloramine loss and nitrifying conditions influenced putative pathogenic bacterial diversity in bulk water and biofilm of a laboratory- and a full-scale chloraminated water distribution systems. Fifty-four reference databases containing full-length 16S rRNA gene sequences obtained from the National Centre for Biotechnology Information database were prepared to represent fifty-four pathogenic bacterial species listed in the World Health Organisation and Australian Drinking Water Quality Guidelines. When 16S rRNA gene sequences of all samples were screened against the fifty-four reference pathogenic databases, a total of thirty-one putative pathogenic bacteria were detected in both laboratory- and full-scale systems where total chlorine residuals ranged between 0.03 - 2.2 mg/L. Pathogenic bacterial species Mycolicibacterium fortuitum and Pseudomonas aeruginosa were noted in all laboratory (i.e. in bulk water and biofilm) and in bulk water of full-scale samples and Mycolicibacterium fortuitum dominated when chloramine residuals were high. Other different pathogenic bacterial species were observed dominant with decaying chloramine residuals. This study for the first time reports the diverse abundance of putative pathogenic bacteria resilient towards chloramine and highlights that metagenomics surveillance of drinking water can serve as a rapid assessment and an early warning of outbreaks of a large number of putative pathogenic bacteria. Graphical abstract: Image, graphical abstract